2018
DOI: 10.1063/1.5004209
|View full text |Cite|
|
Sign up to set email alerts
|

Vacancy defects and optoelectrical properties for fluorine tin oxide thin films with various SnF2 contents

Abstract: Fluorine doped tin oxide (FTO) thin films were deposited on glass substrates by e-beam evaporation. Much higher carrier concentration, broader optical band gap, and average transmittance over 80% were obtained with SnF2 doped SnO2 thin films. Positron annihilation results showed that there are two kinds of vacancy clusters with different sizes existing in the annealed FTO thin films, and the concentration of the larger vacancy clusters of VSnO in the thin films increases with increasing SnF2 contents. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The dependence on H 2 is due to generation of oxygen vacancies by Sn 2+ in the SnO 2 mother structure. This explanation is in agreement with the reported band structure in [46] and explains small variations of energy level values as shown in Fig. 9(c), giving F O energy levels at ~0.4 eV below the CB and V O 2+ energy level at ~0.6 eV above the VB.…”
Section: Defect Structure Characterizationsupporting
confidence: 92%
See 3 more Smart Citations
“…The dependence on H 2 is due to generation of oxygen vacancies by Sn 2+ in the SnO 2 mother structure. This explanation is in agreement with the reported band structure in [46] and explains small variations of energy level values as shown in Fig. 9(c), giving F O energy levels at ~0.4 eV below the CB and V O 2+ energy level at ~0.6 eV above the VB.…”
Section: Defect Structure Characterizationsupporting
confidence: 92%
“…Alternatively, Trani et al [45] ascribed this band in SnO 2 to the appearance of a fully occupied flat energy level lying at about 1 eV above the valence band and an empty level resonant with the conduction band. Moreover, based on positron annihilation experiments, Zhou et al [46] have supported the origin of this 2.5 eV band as electron transitions from a V O + energy hybridized with the conduction band to a V O 2+ energy level.…”
Section: Defect Structure Characterizationmentioning
confidence: 94%
See 2 more Smart Citations
“…11 Zhou et al found reduction in Sn vacancies defects in MASnI 3 solar cells, the carrier injection enhancement, and the energy bandgap widening resulting in suppressing I-V hysteresis. 12 It is challenging to obtain a stable tin-based perovskite cell with higher PCE. 13 In 2012, Chung et al first showed that the solution-processable p-type direct bandgap semiconductor CsSnI 3 can be used for hole conduction in lieu of a liquid electrolyte and the conversion efficiencies of up to 10.2% (8.51% with a mask).…”
Section: Introductionmentioning
confidence: 99%